Developing transformation modules for young inmates in Malaysian prison schools / John Mark Storey and Dr. Esther Jawing - Storey, John Mark; Jawing, Esther (Universiti Teknologi MARA, Kedah, 2024)
Education is a pivotal aspect of correctional programs in prison institutions, aiming to equip inmates with the essential skills and knowledge needed for successful reintegration into society post-release. However, concerns arise regarding the educational experiences of young inmates serving short-term sentences, typically less than one year. This case study addresses these concerns by developing supplementary modules specifically designed for young inmates in a selected prison school. Following the ADDIE framework, the study progressed through three phases. The needs analysis phase, conducted from July 2021 to August 2021, identified the specific requirements of six teachers working in the prison school. This ensured that the modules aligned with the educators' and young inmates' needs and challenges. During the design and development phase, from January 2022 to March 2022, experts provided feedback on the overall module design, content, and activities, refining them for effectiveness. The implementation phase occurred from April 2022 to September 2022, involving 57 students and 4 teachers in the selected prison school. Interviews and observations were conducted to gather data on the students' experiences with the modules. The analysis revealed positive outcomes: students expressed enjoyment, indicating their engagement and interest in the modules. This study has significant implications for the pedagogical approach in prison schools. By showcasing the success and effectiveness of the supplementary modules, it provides insights and guidance for planning fluid and organic teaching and learning activities in similar settings. The findings contribute to ongoing efforts to enhance educational opportunities for young inmates, promoting their successful reintegration into society upon release.